A dimensão urbana dos conflitos contemporâneos e as cidades frágeis: novas perspectivas e práticas - Miklos, Manoela Salem [UNESP] (2015)
At the end of the 1990's, researchers involved on the debate about the new wars introduced the discussion about the urban dimension of the contemporary conflicts to the International Relations discipline. Such discussion fostered new research lines, all of which share the perception that the urban dimension is critical to the understanding of the contemporary conflicts. The city is the place where transnational flows materialize - both legal and illegal, formal and informal, material and immaterial, the place where the challenges of global governance become concrete. The debate about the fragility of the cities is one of the many lines of inquiry that emerge within this framework. This thesis seeks, first, to systematize the literature on the fragile cities from its origins, when it was linked it to the literature on fragile states, to the present. Then, it will demonstrate that the fragile cities are constituted as a new locus of humanitarianism through empirical evidence. The literature on the fragile cities creates new perspectives. Humanitarian aid Institutions inaugurate new practices, appropriating the literature on fragile cities.